2021
DOI: 10.1093/ajcn/nqab078
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality, gut microbiota, and microRNAs associated with mild cognitive impairment in middle-aged and elderly Chinese population

Abstract: Background Diet, the gut microbiota, and microRNAs (miRNAs) have been recognized as factors possibly influencing the pathogenesis of Alzheimer's disease. However, the combined role of diet, the gut microbiota, and miRNAs in mild cognitive impairment (MCI) has not been extensively investigated. Objectives To examine the associations among diet quality, the gut microbiota, miRNAs, and risks of MCI in middle-aged and elderly Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 47 publications
2
54
0
1
Order By: Relevance
“…Table 1 summarizes the clinical and demographic characteristics of the 11 studies. These studies were performed in China [ 23 25 , 27 , 29 , 35 , 45 , 46 ] and U.S. [ 26 , 28 , 47 ], with a total of 378 HC and 427 patients with AD spectrum (AD = 251, MCI = 124, aMCI = 52).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the clinical and demographic characteristics of the 11 studies. These studies were performed in China [ 23 25 , 27 , 29 , 35 , 45 , 46 ] and U.S. [ 26 , 28 , 47 ], with a total of 378 HC and 427 patients with AD spectrum (AD = 251, MCI = 124, aMCI = 52).…”
Section: Resultsmentioning
confidence: 99%
“…The principal coordinate analyses based on both Weighted UniFrac distance and Unweighted UniFrac distances were most frequently measured. In terms of Weighted UniFrac distance, three studies revealed significant differences [ 24 , 29 , 46 ], while four studies revealed no significant differences between HC and AD spectrum [ 23 , 25 , 28 , 45 ]. In terms of Unweighted UniFrac distances, two studies revealed significances [ 24 , 29 ] while four studies revealed no significant differences between HC and AD spectrum [ 23 , 25 , 28 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher adherence to the Dietary Guidelines for Americans, assessed by HEI-2005 or HEI-2010, has been reported to be associated with higher global cognition among Puerto Rican adults living in Boston, and better cognitive performance for White and African Americans from Baltimore, respectively [ 10 , 12 ]. Likewise, in a middle-aged and elderly Chinese population, the Chinese Dietary Guidelines Index-2018 was significantly associated with a lower risk of mild cognitive impairment [ 11 ]. However, our results are inconsistent with the Women’s Health Initiative Memory Study that showed no significant associations between HEI-2010 and cognitive decline in older women [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although initially hypothesized for gastrointestinal disorders [ 102 ], gut microbiome-derived biomarkers have also been considered for psychological and neurodegenerative diseases (i.e., bipolar disorder, multiple Sclerosis, and PD), reporting powerful predictivity and differential diagnosis ability [ 103 , 104 , 105 ]. Regarding AD, promising results have recently been obtained, and Table 1 summarizes the main findings [ 72 , 73 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ] ( Table 1 ). Whilst species of Prevotella and Helicobacter have been shown to be significantly different between APP/PS1 transgenic mice and controls, Actinobacteria and TM7 phylum seem to be more accurate in diagnosing AD when using the triple transgenic mouse model [ 106 , 107 , 109 ].…”
Section: Mainmentioning
confidence: 99%